The right to feel. Intimate visits and sexuality in men’s jails in the Province of Buenos Aires - Oleastro, Inés (Instituto de Altos Estudios Sociales, 2019)
This article analyzes daily life in a prison of the Province of Buenos Aires in relation to masculinities and sexualities. The research suggests the intersection of four fundamental aspects I first explore power relationships inside the prison. Secondly, gender relations in terms of masculinities and sexualities. In the third place the implication of family and affects. And finally, I analyze sexual visits which take place between visitors and inmates, as a form of regulating sexual life in prison in relation with everyday life in prison.